Análise do manejo de áreas protegidas no espaço urbano : diagnóstico e estratégias de gestão ambiental na Microrregião de Campo Mourão-PR - Cardoso, Oséias (2016)
With the concentration of population in urban areas, the existence of free building space became fundamental to bring public spaces about. Among the areas that can be considered free areas, we chose the commitment to explore protected green areas, established for legal documents, which are seen by some governing bodies as conservation units. The first conjectures linked to the problem and to the justification of this research are associated with a scenario of uncertainty mentioning its role in society and the managers lack of knowledge on the condition, or even the functions that these areas need to develop where they are located. As main objective, we seek to develop diagnostic and strategies of environmental manage in urban space, assisting the process of planning, management and administration of these units. The place chosen for this research was the micro-region of Campo Mourão in Paraná, covering the cities of Campo Mourão, Roncador and Corumbataí do Sul. These cities were selected because they were the only in the micro-region with protected areas urban PAs, registered in IAP Paraná Environmental Institute. The theoretical option taken embraces the systemic approach and the integrated landscape. The methodological procedures associated with the moments of diagnosis and analysis were developed in stages: the history of the creation and description of the location, the representation profile, management diagnosis and the characterization of ecological and socio-environmental functions. During the process cartographic products and visual elements were built in the quest to fulfill the research objectives. The results showed that the proper categorization to the special features of the surveyed areas needs to be made, that the geographical condition of these areas associated to the ecological and sócio-environmental functions must be properly absorbed by managers of this process. After the diagnostic procedure and analysis it was possible to infer some propositions which can be considered by managers as a management tool and even by society as a tool to claim their rights